Trust among faculty and students as an essential element of Smart Education System - SHAIKH, NAIM; KASAT, KISHORI; SHINDE, MAHESH (The journal of contemporary issues in business and government, 2021)
The Covid19 pandemic negativity has come up with one silver lining in the educational system, that of more use of smart and intelligent technological interventions in education: Smart and education system. This has sensitised the educators about the kind of technological change that the education systems are about to experience. As with all the technologies smart education system has its pros and cons. However, one of the main impediments in adopting this technological transformation is trust. During the next phases of the pandemic, colleges everywhere must be able to transition to a completely online format at a moment’s notice. Once the COVID-19 crisis ends, the need for agile teaching models will continue, as a potential health or climate crisis may occur at any time. However, getting the technology in place to offer course content online is not enough to ensure robust teaching. This research paper is exploring the importance of ‘trust’ with effective and appropriate use of smart education tools and techniques and establish relationship between ‘Smart education’ and ‘trust’ as well as ‘Evaluation and attentiveness’ and ‘trust’ to ensure broad understanding between the faculty and students as their individual experiences. The paper also focuses on involving ethical practises particularly in evaluation procedure while using smart education system.